2019
DOI: 10.36437/irmhs.2019.2.2.k
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review Study on the Communication between Diabetes and Cancer: The Serious Risk of Cancer in Diabetic Patients

Abstract: Introduction: Diabetes is a chronic metabolic disease which accounts for 15 percent of healthcare spending in the United States. Patients with diabetes have been reported to increase the risk of cancer by 20 to 25 percent compared to those without diabetes. In this study, we intend to examine the relationship between these two diseases by examining several studies. Therefore, this systematic review was conducted to determine the relationship between diabetes and cancer and the risk of developing cancer in diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Empirical studies have shown that quality of life can be considered as an indicator of the quality of health care and is part of the treatment plan, and its measurement in chronic illnesses provides planners with more information about the health status and disease. This information can also be considered useful as a useful guide to improving the quality of care (18). In this study, we reviewed ten articles that examine the quality of life of diabetic patients in an epidemiological fashion.…”
Section: Resultsmentioning
confidence: 99%
“…Empirical studies have shown that quality of life can be considered as an indicator of the quality of health care and is part of the treatment plan, and its measurement in chronic illnesses provides planners with more information about the health status and disease. This information can also be considered useful as a useful guide to improving the quality of care (18). In this study, we reviewed ten articles that examine the quality of life of diabetic patients in an epidemiological fashion.…”
Section: Resultsmentioning
confidence: 99%
“…In general, these complications can cause many illnesses. Most studies have shown that patients with diabetes who are less self-healing have more complications (19)(20)(21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…In 2012, the direct cause of diabetes was 1.5 million deaths, with an inappropriate combination (low physical activity and unhealthy diet) leading to an uncontrollable increase in the prevalence of diabetes in the world, and in 2014, the global prevalence of diabetes among adults over the age of 18 The year was estimated at 9%. and the prevalence of this disease in Iran, according to the statistics released by the health department of the Ministry of Health in a population over the age of 30, is more than 14% or more in the female population, and it is associated with multiple short-term and long-term complications, which in many cases is not reversible and there are many complications such as blindness, neuropathy and cardiovascular discomfort (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38). In diabetic patients, depression is one of the most common psychiatric disorders that depression is a mood that involves rage and escapes from activity or unconsciousness and reluctance, and can affect one's thoughts, behavior, feelings and health, and well-being.…”
Section: Introductionmentioning
confidence: 99%